2023
DOI: 10.3390/molecules28020629
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions of Edaravone in Aqueous Solutions of Ethaline and Glyceline Inferred from Experiments and Quantum Chemistry Computations

Abstract: Edaravone, acting as a cerebral protective agent, is administered to treat acute brain infarction. Its poor solubility is addressed here by means of optimizing the composition of the aqueous choline chloride (ChCl)-based eutectic solvents prepared with ethylene glycol (EG) or glycerol (GL) in the three different designed solvents compositions. The slurry method was used for spectroscopic solubility determination in temperatures between 298.15 K and 313.15 K. Measurements confirmed that ethaline (ETA = ChCl:EG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 75 publications
2
22
0
Order By: Relevance
“…The current study is an extension of the previous investigations regarding the solubility of edaravone in organic solvents [ 72 ] and DES systems [ 71 ]. The main motivation is finding pharmaceutically acceptable systems with elevated solubility of this active pharmaceutical ingredient.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The current study is an extension of the previous investigations regarding the solubility of edaravone in organic solvents [ 72 ] and DES systems [ 71 ]. The main motivation is finding pharmaceutically acceptable systems with elevated solubility of this active pharmaceutical ingredient.…”
Section: Resultsmentioning
confidence: 96%
“…Despite these limitations, DESs are extensively utilized in many applications, including the pharmaceutical industry [ 68 , 69 , 70 ]. In fact, one of our previous studies was focused on the solubility of edaravone in DESs [ 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach, acronymed as COSMO-RS (COnductor-like Screening Model for Realistic Solvents) [120], is designed for bulk systems, in principle, of arbitrary compositions, concentrations, and temperature ranges. That is why this particular framework is selected as a default source of theoretically determined molecular characteristics, as it was already successfully documented in our previous projects [79,83,117,118,[121][122][123][124]. In particular, the COSMO-RS theory implemented in the COSMOtherm package (version 24.0.0) offers a very convenient way to saturate system characteristics and is used as the source of molecular descriptors also in this project.…”
Section: Molecular Descriptorsmentioning
confidence: 99%
“…It has previously been shown that the amount of water in DESs can affect the solubility of the active ingredient. [57] On the other hand, it is well known that the high viscosity of DES may be a limitation for the development of new liquid formulations. For these reasons, different amounts of water have been explored for each of the DESs to reduce the viscosity of the preparations and increase their usability.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that the amount of water in DESs can affect the solubility of the active ingredient [57] . On the other hand, it is well known that the high viscosity of DES may be a limitation for the development of new liquid formulations.…”
Section: Introductionmentioning
confidence: 99%